Southeast Asian Studies in China - Wong, John, 1939-; Saw, Swee-Hock, 1931-2021 (Book collections on Project MUSE., 2007)
Traces the development of Southeast Asian Studies in China, discusses the current status of these studies, examines the problems encountered in the pursuit of these studies, and attempts to evaluate their prospects in the years ahead.